The Imposition of the Final Transfer of Rights to Land and/or Building Tax (PPHTB) in the Sale and Purchase Binding Agreement (PPJB) - Reza Ananda Kurniasari; Siti Malikhatun Badriyah (Jurnal Daulat Hukum, 2022)
The making of a binding sale and purchase agreement (PPJB) before or by a notary is subject to a tax on the transfer of rights to land and/or buildings, one of which is in the form of income tax on land and/or buildings (PPHTB) which is final. This study aims to discuss the imposition of the final PPHTB on the Sale and Purchase Binding Agreement (PPJB). The method used in this study was a normative research method. Normative or library research method was a method used by means of research on library materials or documents with the aim of reviewing existing written regulations. The assessment was carried out using a normative juridical method. The result of this study is that the imposition of the final PPHTB on the Sale and Purchase Binding Agreement (PPJB) is considered inappropriate, because in the making of the Sale and Purchase Binding Agreement (PPJB) the ownership rights to land and/or buildings have not yet been transferred but only occurred when the Sale and Purchase Deed was signed.